Delignification of oil palm empty fruit bunches using deep eutectic solvent in pressurized reactor - Arfat, Md; Mohd Hasbi, Ab Rahim; Rasidi, Roslan; Mustafa, Abu Hasnat (Penerbit Universiti Teknologi Malaysia, 2024)
Although lignin from oil palm empty fruit bunches (OPEFB) is a sustainable bioresource with several value-added uses, it is still difficult to extract lignin from lignocellulosic biomass economically. Lignin fractions are required for high-value applications and subsequently increase the feasibility of lignocellulosic biorefineries. Besides, the remaining cellulose could be further valorized into various chemical products. In this study, the delignification efficiency of OPEFB under inert and pressurized conditions has been studied as an effective pretreatment method for OPEFB. The optimal conditions of the high-pressure reactor to remove lignin from OPEFB were determined to be 80 °C at 30 bars with the presence of deep eutectic solvents (DES). It was identified that pressure affects the removal of lignin with the least amount of structural breakdown and the digestibility of cellulose. The effective removal of lignin from the OPEFB was established under mild conditions employing an inert nitrogen gas pressurized system. This work selectively removes lignin from the OPEFB of palm oil biomass plants using DES under mild extraction conditions. Solid residues were characterized by using FTIR, SEM, TGA, and XRD to investigate fractions under various reaction conditions, such as removal temperature, time, and pressure. The thermal stability of lignin was determined by TGA. In this study, 36.68% of lignin was removed under optimum pressure conditions at the lowest process temperature of 80 °C to determine how these factors influence the efficiency of lignin extraction in a high-pressure reactor.